Optimal transmitter location using multi-scale algorithm based on real measurement for outdoor communication - Karrar Shakir Muttair; Mahmood Farhan Mosleh; Oras Ahmed Shareef (IAES International Journal of Artificial Intelligence (IJ-AI), 2022)
In the era of wireless network communication, the demand for determining the best transmitter (Tx) location is constantly increasing especially in outdoor environments and localization-based services. In this paper, localization optimal location of a Tx has been achieved in electrical engineering technical college by using received signal strength (RSS). We install practical devices in the college to measure the received signal strength in all the college regions. Where each device consists of two pieces which are the AirMAX sector directional antenna and signal broadcast piece (router board). We measured RSS in four directions for each received point in all selected regions using the NetSpot software. An algorithm was created in MATLAB software to determine the average received power (ARP), average signal quality (ASQ) as well as calculate the average coverage (AC) for each Tx device location based on the locations deployed in the real environment. Overall, the results obtained showed that this algorithm effectively demonstrated that it is able to determine the best location of a Tx device compared to other deployed locations in the college. Furthermore, we find large effects when a Tx location changes from one location to another on the RSS because of the surrounding environment effects.